Characteristics of the human resource development and trainings in Vietnamese SMEs and Start-ups - Nguyen, Thanh Tung (2016)
This research is to study several characteristics of human resource development and training in Vietnamese SMEs and start-ups by using qualitative methods. There are three cases studies which was selected thoroughly to be examined. Their characteristics are compared to findings from other Vietnamese and international SMEs by other scholars. The findings indicate that there are consensuses between three case studies and other sample in other studies, but also emphasise some differences, which illustrate the diversity in the picture of SMEs in Viet Nam.